Penggunaan Media Audio Visual Youtube dalam Meningkatkan Keterampilan Berbicara Siswa Kelas III UPTD SDN 24 Batangase Kecamatan Mandai Kabupaten Maros - Firdaus, Andi Mulawakkan; Awaliyah, Irpiya Ainun (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research discusses the use of YouTube media to improve students' speaking skills in class III UPTD SDN 24 Batangase, Mandai District, Maros Regency. This research aims to determine the use of YouTube media in improving students' speaking skills in class III UPTD SDN 24 Batangase, Mandai District, Maros Regency and to make it easier for students to learn through teaching videos on YouTube because they can be accessed anytime and anywhere. This type of research is qualitative research in which the researcher attempts to describe and explore data naturally, in addition to providing an in-depth explanation or evaluation of the research and following research developments based on the problems posed. The data analysis technique used in this research involves collecting three types of data: qualitative data in the form of observation data, interviews and documentation. The data will be analyzed qualitatively. This means that all data will be explained in depth based on the research problem. The results of this research state that the YouTube method can improve the speaking skills of class III students at UPTD SDN 24 Batangase, Mandai District, Maros Regency.